Managerial betrayal: justifying the punishment of Enron’s management - Angelis, Jannis (Revista Economia & Gestão, 2008)
Few interested in corporate affairs can have missed the demise of Enron. The case involved hugely complex transactions designed to appease regulators, analysts and shareholders; and corporate governance, risk management and internal control were sacrificed in favour of profitability and growth. In this paper Ten’s (1987) theory is usedto illustrate the benefit of a combined utilitarian and retributive model for justifying the punishment of Enron’s management. Throughout, the study makes both practical and theoretical observations.